Talking to Cells: Semiconductor Nanomaterials at the Cellular Interface. Issue 4 (26th February 2018) - Rotenberg, Menahem Y.; Tian, Bozhi
Abstract: The interface of biological components with semiconductors is a growing field with numerous applications. For example, the interfaces can be used to sense and modulate the electrical activity of single cells and tissues. From the materials point of view, silicon (Si) is the ideal option for such studies due to its controlled chemical synthesis, scalable lithography for functional devices, excellent electronic and optical properties, biocompatibility, and biodegradability. Recent advances in this area are pushing the biointerfaces from the tissue and organ level to the single cell and subcellular regimes. In this progress report, some fundamental studies are described focusing on miniaturizing the bioelectric and biomechanical interfaces. Additionally, many highlighted examples involve freestanding Si‐based nanoscale systems, in addition to substrate‐bound structures or devices; the former offers new promise for basic research and clinical application. In this report, recent developments in the interfacing of neuronal and cardiac cells and their networks are described. Moreover, a brief discussion of the incorporation of semiconductor nanostructures for interfacing nonexcitable cells in applications such as probing intracellular force dynamics and drug delivery is included. Finally, several directions for future exploration are suggested. Abstract : Interfacing biological components with semiconductors is a growing area with numerous opportunities for fundamental studies and applications. In this progress report, materials and techniques for enabling miniaturized bioelectric and biomechanical interfaces are discussed. Recent developments in interfacing of neuronal and cardiac cells and their networks are described, and incorporation of semiconductor nanostructures for probing the dynamics in nonexcitable cells is briefly reviewed.